Personal psychology : - Baltus, Rita K. (Glencoe/McGraw-Hill, 2000)
The fifth edition of this popular text-workbook prepares students to successfully meet many challenges in their personal lives and careers. The text equips students with a basic understanding of psychological principles and shows how to apply these principles in a variety of situations. Personal Psychology for Life and Work emphasizes the need for developing problem-solving and communications skills and for learning to effectively manage stress and conflict.